Do LGUs’ non-financial support instruments matter to new firm formation? - Skica, Tomasz; Rodzinka, Jacek; Golejewska, Anna; Suchanek, Michał (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The topic of policies supporting entrepreneurship implemented by local government units (LGUs) is the subject of many studies. At the same time, despite of many approaches and attempts to clarify this issue, this problem has not been exhausted and presented in a conclusive manner. Aim: The main goal of article is to find out which of the non-financial entrepreneurship support instruments used by local government units (LGUs) in Poland effectively support new firms formation. Results: The research proved that non-financial instruments at the disposal of communes are effective in the processes of stimulating entrepreneurship. The effects of their implementation are conditioned by the generic category of the LGUs, the quality of the institutional environment as well as the involvement of local actors in the process of designing development policies. The research proved that the highest effectiveness of non-financial instruments was noted in relation to cities with poviat rights, which confirms inability to treat individual instruments as universal tools, independent of the specificity of the local government unit applying it.